Cuidado ao adulto por equipe de saúde da família: análise a partir do modelo de atenção às condições crônicas - Neves, Gabriela Leal (2024)
Introduction: Chronic diseases comprise a set of chronic conditions, usually causing disabilities and a long care process. In this scenario, the importance of the Chronic Conditions Care Model is highlighted, considering individual characteristics, health services, and the concentration of each population group. Thus, it is aligned with the Sustainable Development Goals, proposing actions to prevent diseases and promote health. Objective: To analyze the care provided to adults with chronic diseases in the context of the Family Health Strategy in two municipalities in the State of Rio Grande do Sul, from the perspective of the Chronic Conditions Care Model. Methodology: This qualitative research used an excerpt from the database referring to the care of adults with chronic diseases in the Family Health Unit of the research entitled "Communication in the work process in the care of children and adults with chronic diseases in the Family Health Strategy". Data collection for the matrix survey was carried out with physicians and nurses from Family Health Units, between October 2017 and February 2018, in two municipalities in Rio Grande do Sul. It was carried out through semi-structured interviews, non-participant observation, and searches for documents and records in the information systems of the municipalities. Between June and July 2024, the individual narratives were returned to the research participants, seeking to complement the data collection and analysis period with possible modifications to the actions. The thematic analysis proposed by Braun and Clarke was implemented. The matrix project has been approved by the Ethics Committee for Research with Human Beings of the Federal University of Rio Grande, with Opinion N. 65/2017 and CAAE N. 4677317.0.1001.5324, and is conducted respecting the ethical precepts of research with human beings. Results and discussion: There was a predominance of nurse participants, with team coordination functions and technical responsibility. The activities are developed mainly through medical and nursing consultations, welcoming, health groups and home visits. It is noted that actions are planned with greater attention to the demands of users to the detriment of programmed care, which need to be balanced for the implementation of the care model. The nursing consultation is presented as a potential for the longitudinality of care and the clinical management of health conditions. There are difficulties in the infrastructure and physical environment of the units, reflecting in the barriers to the paradigm shift of the current hegemonic model. Conclusion: The development of the research enabled the visibility of care practices for adults with chronic diseases in the Family Health Units, highlighting the barriers and possibilities for the operationalization of the Care Model for Chronic Conditions and the strengthening of the health care network in the scenarios listed. It is expected to contribute to the construction of knowledge in nursing and to the strengthening of health services through discussions on the theme with professionals and managers. Thus, it is estimated that the reflection and problematization of the aspects inherent to the care of adults living with chronic diseases in the context of Family Health Units is estimated.